Impacts of feral horses in the Australian Alps and evidence‐based solutions. (30th January 2019) - Driscoll, Don A.; Worboys, Graeme L.; Allan, Hugh; Banks, Sam C.; Beeton, Nicholas J.; Cherubin, Rebecca C.; Doherty, Tim S.; Finlayson, C. Max; Green, Ken; Hartley, Renée; Hope, Geoffrey; Johnson, Chris N.; et al.
Summary: New evidence of impacts by feral horses in Australia's alpine parks systems confirms they endanger threatened species and extensively damage critically endangered bog communities that could take millennia to recover. These impacts are not confounded by effects of deer and accumulate over time, even when only a small number of feral horses ( 100) are present. With protected areas representing only a small proportion of the area of the Australian states of New South Wales (9.3%) and Victoria (17%), allowing feral horses to degrade reserves is not a reasonable management compromise, is contrary to the purpose of the protected area system and conflicts with international obligations. Modelling and decades of management experience indicate that trapping alone does not control feral horse numbers. Trapping and fertility control can work in small populations, but not when there are several thousand horses in remote areas. Aerial culling is needed to cost‐effectively and humanely control feral horse populations. The relatively small amount of suffering feral horses experience during a cull is outweighed by (i) avoiding suffering and death of horses from starvation and thirst, (ii) avoiding the suffering of native animals displaced by horses and (iii) avoiding the ethical concerns of driving threatened species towards extinction. Objections to aerial culling on welfare and cultural grounds are contradicted by evidence. Improving knowledge in the general community about what is at stake is long overdue because without this knowledge, small groups with vested interests and unfounded claims have been able to dominate debate and dictate management actions. As a result of ineffective management, horse populations are now expanding and causing well‐documented damage to Australia's alpine parks, placing at risk almost 10M spent on restoration after livestock grazing ended. The costs of horse control and restoration escalate the longer large horse populations remain in the alpine parks. It is crucial that feral horse numbers are rapidly reduced to levels where ecosystems begin to recover. Aerial culling is needed as part of the toolbox to achieve that reduction.